New Carrier Made from Glass Nanofibres for the Colorimetric Biosensor of Cholinesterase Inhibitors - Matějovský, Lukáš; Pitschmann, Vladimír (Biosensors, 2018)
Cholinesterase inhibitors are widely used as pesticides in agriculture, but also form a group of organophosphates known as nerve chemical warfare agents. This calls for close attention regarding their detection, including the use of various biosensors. One such biosensor made in the Czech Republic is the Detehit, which is based on a cholinesterase reaction that is assessed using a colour indicator-the Ellman's reagent-which is anchored on cellulose filter paper together with the substrate. With the use of this biosensor, detection is simple, quick, and sensitive. However, its disadvantage is that a less pronounced yellow discoloration occurs, especially under difficult light conditions. As a possible solution, a new indicator/substrate carrier has been designed. It is made of glass nanofibres, so the physical characteristics of the carrier positively influence reaction conditions, and as a result improve the colour response of the biosensor. The authors present and discuss some of the results of the study of this carrier under various experimental conditions. These findings have been used for the development of a modified Detehit biosensor.
Keywords: sklo; biosenzitivní techniky; Glass; glass fibre filter paper; cholinesterasové inhibitory; Cholinesterase Inhibitors; nanovlákna; biosensor; Nanofibers; Ellman’s reagent; cellulose filter paper; cholinesterase reaction; Biosensing Techniques